2009
DOI: 10.1111/j.1540-8183.2009.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Implantable Wireless Cardiac Monitoring Platform Integrated with an FDA‐Approved Cardiovascular Stent

Abstract: Continuous monitoring of blood pressure from a minimally invasive device in the pulmonary artery can serve as a diagnostic and early warning system for cardiac health. The foremost challenge in such a device is the wireless transfer of data and power from within the blood vessel to an external device while maintaining unrestricted flow through the artery. We present a miniaturized system, which is attached to the outer surface of a regular or drug-eluting FDA-approved stent. When expanded, the stent maintains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Non-catheter-based sensors are often incorporated onto stents and are among the more advanced of this class [ 82 ]. Both are contained completely within the body (i.e., without any external anchors, leads or probes) and transmit transdermal signal to an external monitoring device via a telemetry device that utilizes radio waves [ 113 , 114 ].…”
Section: Bnp Monitoringmentioning
confidence: 99%
“…Non-catheter-based sensors are often incorporated onto stents and are among the more advanced of this class [ 82 ]. Both are contained completely within the body (i.e., without any external anchors, leads or probes) and transmit transdermal signal to an external monitoring device via a telemetry device that utilizes radio waves [ 113 , 114 ].…”
Section: Bnp Monitoringmentioning
confidence: 99%
“…Implanting sensors in the heart and monitoring blood flow could help in the diagnosis of a variety of cardiac ailments. Chow et al 87 developed an implantable cardiac monitoring system that was integrated with a cardiovascular stent. The system consists of an FDA-approved stent tailored with a miniature cardiac pressure sensor and wireless transmitter.…”
Section: Biosensor Integrated Cardiovascular Stentsmentioning
confidence: 99%
“…The integrated system with a FDA approved stent facilitates wireless transmission and power transfer. The in vivo experiments resulted in successful wireless data transfer from the implanted device at reception distances of 50 cm which was inserted at a depth of 3.5 cm . Green et al demonstrated the wireless monitoring of the accumulation of biliary sludge using a plastic stent integrated with a sensor.…”
Section: Stentsmentioning
confidence: 99%